Efficacy of Two Rotary NiTi Instruments in Removal of Resilon/Epiphany Obturants - Mohebbi, Pooneh (Iranian Endodontic Journal, 2012)
Introduction: The success of endodontic retreatment is related to the complete removal of the obturation material from the root canal system. The aim of this study was to evaluate the efficacy of Mtwo R and ProTaper retreatment files in removing the Resilon/Epiphany system with or without chloroform during retreatment. Materials and Methods: Sixty distal roots of first mandibular molars were prepared and laterally condensed with Resilon/Epiphany, then divided into four groups (15 each for retreatment): 1) Mtwo R/solvent; 2) Mtwo R; 3) ProTaper D/solvent; and 4) ProTaper D. The cleanliness of the canal walls was evaluated using radiography; a stereomicroscope and SEM. Data were subjected to ANOVA and Student’s t-test. <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA;" lang="X-NONE">Results: Neither rotary system performed better than the other when considering the whole root canal, with or without solvent. In the apical portion, ProTaper/solvent showed the best result (P<0.05). <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">Conclusion<span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: X-NONE;" lang="X-NONE">:<span style="font-family: "Times New Roman","serif"; color: black; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;" lang="X-NONE"> In Resilon/Epiphany retreatment cases, ProTaper/solvent was better in the apical portion; however when considering the whole canal, Mtwo R and the ProTaper D series had the same performance.